Designing a Food Ordering Application System at Esthetic Cafe Using the Laravel Framework - Arifin, Ilham; Hayadi, B. Herawan; Pratama, Gelard Untirtha (PT Mattawang Mediatama Solution, 2025)
The rapid advancement of information technology has significantly influenced the culinary business sector, particularly in enhancing service efficiency and customer experience. Esthetic Cafe, as a small-to-medium-sized enterprise, faces challenges in streamlining its food ordering process, which has traditionally been conducted manually. This research aims to design and develop a web-based food ordering application system using the Laravel framework to improve operational workflow, minimize order errors, and enhance customer satisfaction. The study adopts the Research and Development (R&D) methodology and implements the Waterfall model to guide the software development life cycle. The stages include requirements analysis, system design, implementation using Laravel, system testing with black box methods, and real-world deployment. The Laravel framework was chosen due to its MVC architecture, scalability, security features, and strong community support. The system provides core functionalities such as user registration and login, menu browsing, cart management, order placement, table selection, simulated payment processing, and transaction history tracking. For administrators, the system includes modules for product and category management, order confirmation, and transaction monitoring. The user interface was designed to be intuitive and responsive, focusing on user convenience and accessibility. Testing results from twelve black box scenarios demonstrated that all system features operated as expected, with successful interactions and accurate system responses. No major errors were identified, confirming the reliability and functionality of the application. In conclusion, the implementation of this food ordering system significantly improves service quality and operational efficiency at Esthetic Cafe. The system also provides a digital solution that supports the business's transition into the digital era. This study shows that web-based applications developed with Laravel can effectively meet the technological needs of small culinary businesses and support sustainable digital transformation.